Evaluacion de una vacuna contra la diarrea por Escherichia coli K99¿ en condiciones controladas de produccion - Rodriguez, N.=700 1 Gonzalez, R.; Talavera, A.
(Es, En)
Ilus., 21 ref.
Keywords: GANADO BOVINO; ENFERMEDADES INFECCIOSAS; COLIBACILOSIS; ESCHERICHIA COLI; VACUNACION; VACA; GESTACION; CUBA